The role of obligation of information in consumer protection from pharmaceutical materials - Ouis, Maya (Journal of Human Sciences, 2021)
The obligation of information is considered one of the basic obligations established to protect the consumer who is the weak party, as it contributes to achieving the safety of the consumer and enlightening his will, especially in the field of pharmaceutical substances that are considered dangerous and vital at the same time, and when it is the responsibility of the pharmacist as an intervening person to inform the consumer of all necessary information and data related to their use to reduce their dangers, and therefore the Algerian legislator had to strengthen this protection to confront the pharmacist’s failure to his obligation of information.